Comparison of morbidity and performance among stressed feeder calves following vaccination with pyramid™ MLV 4 or Pyramid™ 4+Presponse® SQ - S. Ives; James S. Drouillard; David E. Anderson; Gerald L. Stokka; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1999)
A study was conducted to compare performance, morbidity, retreatment percent, and mortality in stressed heifer calves during the receiving and growing phases after receiving either Pyramid™ MLV 4 or Pyramid™ 4+Presponse® SQ on arrival at a feedlot research facility. Vaccination with Pyramid 4+Presponse SQ (a 4-way viral modified live vaccine with a Pasteurella haemolytica bacterin-toxoid) tended to reduce the incidence of bovine respiratory disease (P=.2) and reduced retreatment rate (P<.06).
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Morbidity; Performance; Feeder calves; Pyramid™ MLV 4; Pyramid™ 4+Presponse® SQ